Language of actions: The effects of teacher's kinesics on student learning and learning environment - Taliya Sajjad; Humaira Fayyaz Khan; Rahila Yasmeen; Arfaa Waqas (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: A teacher's appropriate use of nonverbal communication skills, mainly kinesics, can play a crucial role in the success of the students. Medical educators are unaware of the effective use of nonverbal communication as an instructional skill that can be used to engage learners, balance learners' participation by controlling the classroom environment, and motivate them to have a passion for learning. The purpose of the study was to explore the students' perceptions regarding the effect of teachers' kinesics on students' learning and their learning environment. This can be helpful for teachers in modifying their teaching styles and delivering quality education. MATERIALS AND METHODS: A qualitative study with an exploratory design was conducted at a private medical institute in 2021 for a duration of 6 months. Fourteen medical students volunteered to participate in the study. Focus group discussions were conducted with the students to explore the experiences of the medical students regarding the use of nonverbal communication skills by their teachers and its effect on their learning in the classroom. The data collected was analyzed manually. RESULTS: The results of the study revealed that teachers' nonverbal behaviors in the classroom significantly influence students' motivation, engagement, and learning in the classroom. Students preferred interaction with the teachers who were friendly and confident and used their nonverbal communication skills (eye contact, facial expressions, hand gestures) effectively, compared to strict and judgmental teachers. CONCLUSION: Teachers need to motivate their students by improving their teaching styles and incorporating nonverbal behaviors positively in the classroom. By creating an impactful learning environment, students' participation and learning will increase, which will, in turn, improve their academic performance.